Best Practices For Choosing Non-Intrusive But Effective CAPTCHAs - Setia Budi (Jurnal Informatika, 2013)
Completely Automated Public Turing Test to Tell Computers and Humans Apart (CAPTCHA) is has become a part of computer security standard in order to distinguish humans from computers. This paper mainly discusses usability and robustness issues in CAPTCHA design and implementation. A brief introduction about CAPTCHA and some attempts to defeat CAPTCHA, including how to deal with it are also described in this paper.